Capsaicinoid and capsinoids as an ergogenic aid: A systematic review and the potential mechanisms involved - de Moura e Silva, Vilton E.L.; Cholewa, Jason M.; Billaut, François; Jäger, Ralf; de Freitas, Marcelo C.; Lira, Fabio S. [UNESP]; Rossi, Fabrício E. (Human Kinetics, 2021)
Context: Capsaicinoids and capsinoids (CAP) are natural substances found primarily in chili peppers and other spicy foods that agonize the transient receptor potential vanilloid-1 in the mouth, stomach, and small intestine. Several studies have shown CAP to be a potential antiobesity agent and to exhibit an analgesic effect in both rodents and humans. However, there is no scientific consensus about the effects of CAP on physical exercise performance and its physiological mechanisms of action. Purpose: This systematic review aimed to better elucidate the effects of CAP compounds as ergogenic aids and to discuss underlying mechanisms of action by which this supplement may potentially enhance endurance performance and muscular strength. Conclusions: Among 22 studies included in the review, 14 examined the effects of capsaicinoid or capsinoid compounds on endurance and resistance exercise performance in animals, with 9 studies showing benefits on performance. In humans, 8 studies were included: 3 demonstrated significant acute endurance benefits and 2 showed acute resistance exercise performance benefits compared with a placebo condition. Therefore, while more mechanistic studies are necessary to confirm these outcomes in humans, the available scientific literature appears to suggest that these compounds could be considered an effective nutritional strategy to improve exercise performance.
Keywords: Endurance; Performance; Preworkout; Resistance exercise; Strength; Supplementation